Health Promotion Program: from theory to practice - Fertman, Carl I, Allensworth, Diane DeMuth (Jossey-Bass, 2010)
Health Promotion Programs introduces the theory of health promotion and presents an overview of current best practices from a wide variety of settings that include schools, health care organizations, workplace, and community. The 43 contributors to Health Promotion Programs focus on students and professionals interested in planning, implementing, and evaluating programs that promote health equity.